LINGUISTIC ERRORS OF BRAZILIAN STUDENTS WHEN LEARNING RUSSIAN AS A FOREIGN LANGUAGE (BASIC LEVEL) - Medina, Joao Paulo Sabadin Santos T.; Medina, Suellen Martins; Budnik, Ekaterina A. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article examines the errors in the basic level regarding the interference of the Portuguese language when Brazilian students learn Russian as a foreign language and offers the methodic to predict and avoid them. For this, authors compare the phonetic systems of Russian and Brazilian Portuguese as well as the main grammar units and structures that form the linguistic minimum on the basic level. Then, using the comparative analysis the errors in the students’ speech are predicted and interpreted. The results of theoretical comparison are compared to the actual and real errors. In the phonetic plan authors figure out significant difference in the signs of hardness, softness, place of articulation, mode of articulation and nasalization, and not big difference in acoustic signs and duration of sounds. In the grammatical field the results point out to a new and optimal order in teaching the cases. Also the necessity to adapt different grammar understanding of Russian verbal structure to the Brazilian one is described regarding the preposition and type of complement and the verb aspects. Authors developed exercises to help students overcome such errors more efficiently and in less time.